Sobre los contenidos gramaticales en el aula de lengua extranjera - Campos Carrasco, Nuria; Devís Márquez, P. Pablo (Verbum – Analecta Neolatina, 2008)
The role of grammar in the foreign language classroom has been widely questioned in language teaching methodology. The positions have oscillated between those who have rejected the possibility of including grammar contents and those that have used grammar like a kernel of the learning process. The work that we present here is based on two fundamental ideas: (1) grammar must be understood like an instrument for learning, and (2) the concept of descriptive grammar must be replaced by the one of pedagogical grammar, directed to complete the assimilation of linguistic contents as a vehicle of communication. We develop a new proposal for teaching grammar that will have to contribute to the definitive location of grammar contents in the process of learning a foreign language.